Changes of plasma fibronectin and fibronectin-fibrin complexes in dams of stillborn dairy calves - Paulina Jawor; Dorota Krzyżanowska-Gołąb; Joanna Bajzert; Tadeusz Stefaniak; Iwona Kątnik-Prastowska (Irish Veterinary Journal, 2020)
Abstract Background Fibronectin (FN) is a large (450–500 kDa), multidomain and multifunctional glycoprotein existing in mammalian tissues. Some fibronectin (FN) molecular forms might be involved in biological processes occurring within the perinatal period, such as tissue remodeling, coagulation, and repair. Results In this study fibronectin (FN) and fibrinogen (Fb) concentrations and FN-fibrin complexes occurrence and its relative amounts with increasing high molecular masses were respectively determined by ELISA, heat precipitation, and SDS-agarose-immunoblotting methods. Plasma samples from three groups of dams with: 1) singleton stillborn calf without or with negligible autolytic changes in internal organs (DSBn), 2) singleton stillborn calf with advanced autolytic changes in internal organs (DSBa), 3) singleton live-born control calf (DC), and 4) a group of cows during mid to late lactation (LC) were analyzed. Maternal plasma FN concentration in the DSBn and DSBa groups was significantly lower than in the LC group. The plasma samples of DSBa showed a significantly lower FN concentration than in the DC group. Plasma Fb concentration was significantly higher in the DSBa and DSBn, than in the LC group. FN immunoblotting of the cow plasma samples revealed, besides an FN-dimer band, the presence of supramolecular FN-fibrin bands corresponding to FN-fibrin complexes with increasing molecular masses: up to 5 bands from 750 kDa to 1900 kDa in the DSBn and DSBa plasma samples, two bands of 750 and 1000 kDa in the DC group, and only the smallest one of 750 kDa in the LC group. Conclusions The observed low FN concentration and occurrence of supramolecular FN-fibrin complexes (1000 kDa and more) in the maternal plasma comparing to cows in lactation might have been associated with periparturient changes in tissues. The presence in maternal plasma of high-molecular FN-fibrin complexes (1300–1900 kDa) arouse the question if this is the consequence of calf perinatal mortality.